EFEKTIVITAS KERJA PEGAWAI NEGERI SIPIL KANTOR KELURAHAN DI KECAMATAN MALALAYANG KOTA MANADO - Hastuti, Mei (HOLISTIK, Journal Of Social and Culture, 2013)
The work effectiveness of the employee highly determines the success of an organization or an institute. To achieve such effectiveness, there we find several factors such as payment motivation and work discipline. High working motivation can result in a good work effectiveness. Likewise the payment offering and work discipline, these two both have an effect toward the work effectiveness of the civil servant. Dereliction toward these variables has an effect on the deterioration of employee’s behavior in doing their work or their service to society. This research aims to know the effect of motivation, payment, and work discipline toward the work effectiveness of the civil servant in subdistrict office of Malalayang District, Manado City. The result of the research shows that those who have high motivation both intrinsic and extrinsic motivation indicate the more effective result in working rather than those who are less motivated. Keywors : motivation, work, discipline